Etiopatogeneza i terapia zaburzeń odżywiania się w perspektywie rodzinnej - Palus, Katarzyna (Wydawnictwo Naukowe UAM, 2006)
Many clinicians have stressed the role of family interactions and family dynamics in the onset, development and maintenance of anorexia nervosa and bulimia nervosa. The aim of this article is to provide a brief description of family features associated with eating disorders and family-based treatment of anorexia nervosa and bulimia nervosa. Family systems approaches explain that the onset and maintenance of eating disorders can be understood within the context of dysfunctional family interactions. This paper presents the Maudsley model of family therapy for children and adolescents with anorexia. The usefulness of family-based treatment of eating disorders lies in not attaching blame to parents but in stressing their important role in therapeutic process. The work with families is an effective way of treatment for young patients, but it does not mean that the family caused the problem. It is noteworthy that a family oriented approach is a component of total program that also addresses the biological, individual and social levels of the patients' functioning.
The etiopathogenesis and therapy of eating disorders in the family perspective